Load transmission via the supraspinatus cord prevents muscle fatty degeneration, a biomechanical study - Omar E. Rodriguez-Alejandro, MD; Bethany G. Ricci, BS; Christopher C. Schmidt, MD; Sean P. Cooke, BS; Austin J. Cook, MS; Justin G. Buce, MS; Joshua D. Dworkin, MD; Mark C. Miller, PhD; Patrick J. Smolinski, PhD (JSES International)
Background: Location of small- to medium-sized (<30 mm) rotator cuff tears can predict (supraspinatus [SS]) muscle fatty degeneration. It has been hypothesized that SS fatty degeneration occurs because of loss of force transfer by either the coracohumeral ligament (CHL) or the SS cord. The CHL is the anterior insertion of the rotator cable theorized to carry rotator muscle force to the humerus. In this study, we aimed to map the anatomic insertions of the CHL and superior rotator cuff onto the humeral head and then sequentially release the footprint to determine which structures are the most critical for force transmission. Methods: Twenty fresh-frozen cadaveric specimens (average age 69 ± 10 years, 9 males) were tested in a shoulder simulator under physiological conditions at 0° and 30° of shoulder abduction. After cyclic loading, shoulder abduction force and glenohumeral translation were measured for the native condition and after each humeral footprint release. Ten specimens were assigned randomly to a CHL-first footprint release with sequential release of the SS cord, SS strap, and infraspinatus tendons. The other 10 specimens underwent an SS cord-first footprint release, with sequential release of remaining insertions. Following mechanical testing, soft tissue cross-sectional dimensions and footprint widths, lengths, and areas were scanned for three-dimensional modeling and dimensionally quantified. Results: An SS cord-first release decreased abduction force by 10% at 0° of abduction and 22% at 30° (P = .047); further, releasing the CHL did not influence the abduction force values (P ≥ .091). A CHL first-release or a CHL release after an SS cord release did not result in a decrease in abduction force (P ≥ .081). However, the abduction force with a subsequent SS cord release did significantly decrease (P ≤ .047). The average anterior-to-posterior humeral footprint widths of the CHL, SS cord, SS strap, and infraspinatus tendons were 0 mm-3 mm, 3 mm-11 mm, 11 mm-20 mm, and 20 mm-40 mm behind the bicipital groove, respectively. Conclusion: The SS cord, and not the CHL, is the key structure responsible for the transmission of anterior shoulder abduction force. Relating the clinical tear location with the study’s humeral footprint results indicates the SS cord is intact in small- to medium-sized rotator cuff tears without SS fatty degeneration. Repairing the SS cord in small to medium rotator cuff tears could be efficacious in improving abduction strength and preventing SS muscle fatty degeneration.